Pedagogical Opportunities of Media Resources in a Digital Media Educational Environment - Zakhro Umarova (Newinera Publisher, 2020)
Today, in XXI century using digital media and media resources in learning and teaching process become a vital. Media become powerful tool in educational process and it gives opportunities gaining effectiveness of teaching and learning process. Majority surveys, which were held in different countries and regions, are showing high quality education results proving that digital media and media resources are effective means in educational process. This article reveals the pedagogical possibilities of media resources in the digital media educational environment.